Beyond profit How sustainable consumer behavior shapes the longevity of family businesses - Khaled Alshaketheep; Hind Al-Ahmed; Ahmad Shajrawi; Ahmad Mansour (Acta Psychologica, 2025)
The research establishes sustainability-related consumer conduct as a foundational force which determines family business duration while establishing sustainability as both ethical and strategic. The proposed research established a dual-mediated framework which demonstrates sustainable consumer orientation (SCO) is linked to improved family business sustainability strategies (SSFB) and brand reputation (BR) thus strengthening long-term firm performance and high-performance indicators. The authors conducted a survey of 700 Jordanian respondents which used structural equation modeling (SEM) through SmartPLS for analysis. Relational exchange with stakeholders functions as a significant predictor for building SSFB and developing FV which acts as both intermediate forces between consumer values and business outcomes. CSP demonstrated a direct relationship to brand reputation which then affected consumer loyalty and performance indicators. This study contributes to theoretical knowledge by resolving the intention–behavior difference and defining the relationship between consumer trust and authenticity for the sustainability of family businesses. Practically, it offers insights for family-owned firms on leveraging generational leadership, transparent communication, and digital storytelling to build credibility and long-term consumer loyalty in increasingly skeptical markets.